Study on an Energy-storage VRF Air Conditioning System - Meng Jianjun; Wu Weidong; Tang Hengbo; Zhang Hua (Zhileng xuebao)
In order to improve the refrigerating capacity and coefficient of performance (COP) of system in summer and reduce the damping of heating capacity in winter, a novel variable refrigerant flow (VRF) system/unit with both cold and heat storage was developed in this work, and the performance of the system was experimentally investigated under the various operating modes, i.e. ice-storage, cold-release, heat-storage, heat-release. The experimental results showed that when the system worked continuously about 8 hours under the ice-storage mode (during off-peak period at night in summer), the cooling capacity stored in the ice layer was up to around 380 MJ, which could be used to increase the subcooling degree of the system running in the day, and in case of about 35 mm of the ice thickness outside the coil, the system could work incessantly about 8 hours under the cold-release mode (during peak period of electricity). Compared with the conventional air conditioning system, the cooling capacity of the system was increased by 29% and the COP was increased to 136.4%. In winter, hot water was stored in the energy-storage tank during off-peak period at night; under the heat-release operating mode in the daytime, the problems such as heating capacity deceleration and frosting of the unit were relieved by increasing the compressor suction and evaporating temperatures of the system.